THE ORDER OF FORMATION OF FINANCIAL RESULTS AND THE SYSTEM OF INDICATORS. - Kodirov Shukhratbek Kutbidinovich; A.T.Mamajonov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the authors discussed the method of forming financial results and the system of indicators. Basically, the types of financial results, their calculation were discussed.